Coated particles and conductive materials containing same

JP7634978B2Active Publication Date: 2025-02-25NIPPON CHEMICAL IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020202891
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-12-07
Publication Date
2025-02-25
Estimated Expiration
2040-12-07

AI Technical Summary

Benefits of technology

【0011】 本発明の被覆粒子は、絶縁性粒子として用いるシリカ粒子の表面にスルホン酸基を有するシランカップリング剤の縮合物が化学結合を介して固定されている粒子を用いているので、シリカ粒子の表面に強固に固定化されて存在するスルホン酸基に起因して、導電性粒子に対して優れた密着性を有する。 このような本発明の被覆粒子は、高い接続信頼性を有しうる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634978000001
    Figure 0007634978000001
  • Figure 0007634978000002
    Figure 0007634978000002
  • Figure 0007634978000003
    Figure 0007634978000003
Patent Text Reader

Abstract

To provide coated particles having improved adhesion between insulative particles and conductive particles.SOLUTION: There are provided coated particles where the surface of conductive particles having a metal film formed on the surface of core material particles is coated with insulative particles, in which the insulative particles are particles where a condensate of a silane coupling agent having a sulfonic acid group is fixed to the surface of silica particles through a chemical bond. The core material particles are preferably a composite material of a resin or an organic matter and an inorganic matter, and the metal film is preferably at least one film selected from nickel, palladium, gold, a nickel alloy, a palladium alloy and a metal alloy.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated particles in which conductive particles are coated with an insulating layer, and to a conductive material containing the same. [Background technology]

[0002] 2. Description of the Related Art Conductive particles, which are resin particles having metals such as nickel and gold formed on the surfaces thereof, are used as conductive materials such as conductive adhesives, anisotropic conductive films, and anisotropic conductive adhesives. In recent years, with the further miniaturization of electronic devices, the circuit width and pitch of electronic circuits are becoming smaller and smaller. Accordingly, conductive particles with small particle diameters are required for use in the above-mentioned conductive adhesives, anisotropic conductive films, anisotropic conductive adhesives, etc. When such small particle diameter conductive particles are used, the amount of conductive particles must be increased to improve the connectivity. However, when the amount of conductive particles is increased, a short circuit occurs due to conduction in an unintended direction, i.e., conduction in a direction different from that between the opposing electrodes, and it is difficult to obtain insulation in that direction. In order to solve this problem, insulating coated conductive particles are used in which the surfaces of the conductive particles are coated with an insulating material to prevent contact between the metal layers of the conductive particles.

[0003] For example, Patent Document 1 describes coated particles in which a particle having a surface made of a conductive metal is used as a core, and the surface of the particle is partially modified with organic particles made of an organic compound containing a functional group that has a binding ability to the metal, and it is described that the organic compound has a positive or negative charge. Patent Document 2 describes coated particles similar to those described in Patent Document 1. The document describes that the coated particles form a single-layer coating layer by chemically bonding insulating fine particles to particles having a surface made of a conductive metal via functional groups that have binding properties to metals. The document describes that coated particles having such a configuration can be thermocompressed between electrodes to melt, deform, or peel off the insulating fine particles, thereby exposing the metal surface of the metal-coated particles, thereby enabling conduction between the electrodes and obtaining connectivity. Patent Documents 1 and 2 exemplify ammonium groups and sulfonium groups as the functional groups.

[0004] Patent document 3 also describes that by applying insulating resin microparticles, which have on their surface a hetero element or functional group that has a bonding strength with a metal, to the surface of a metal-coated particle and then heating the applied particles, anisotropic insulated conductive particles having an insulating layer that does not have a particle shape on the surface of the metal-coated particle can be obtained. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2002 / 035555 Brochure [Patent Document 2] International Publication No. 2003 / 025955 Brochure [Patent Document 3] International Publication No. 2005 / 109448 Brochure Summary of the Invention [Problem to be solved by the invention]

[0006] In the case of conductive particles coated with insulating particles, the improvement of adhesion between the insulating particles and the conductive particles has been an issue. Since the adhesion between the insulating particles and the conductive particles is important for achieving electrical conduction between the opposing electrodes while obtaining insulation in a direction different from that of the opposing electrodes (hereinafter, also referred to simply as connection reliability), there is a demand for the development of coated particles with even better adhesion between the insulating particles and the conductive particles.

[0007] Therefore, an object of the present invention is to provide coated particles having improved adhesion between insulating particles and conductive particles, and a conductive material containing the same. [Means for solving the problem]

[0008] In view of the above-mentioned circumstances, the inventors have conducted extensive research and have discovered that, in coated particles in which the surface of conductive particles having a metal coating formed on the surface of a core material is coated with insulating particles, when the insulating particles are silica particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface of the silica particles via a chemical bond, the coated particles have excellent adhesion between the insulating particles and the conductive particles, and have thus completed the present invention.

[0009] That is, the first invention that the present invention provides is a coated particle in which the surface of a conductive particle having a metal coating formed on the surface of a core particle is coated with an insulating particle, characterized in that the insulating particle is a particle in which a condensate of a silane coupling agent having a sulfonic acid group is fixed to the surface of a silica particle via a chemical bond.

[0010] A second aspect of the present invention is a conductive material comprising the coated particles of the first aspect of the invention and an insulating resin. Effect of the Invention

[0011] The coated particles of the present invention use silica particles used as insulating particles, on the surface of which a condensate of a silane coupling agent having a sulfonic acid group is fixed via a chemical bond. Therefore, due to the sulfonic acid group firmly fixed on the surface of the silica particles, the coated particles have excellent adhesion to conductive particles. Such coated particles of the present invention can have high connection reliability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described based on preferred embodiments. The coated particles of this embodiment are conductive particles having a metal coating formed on the surface of a core particle, the surface of which is coated with insulating particles, and are characterized in that the insulating particles are particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface of a silica particle via a chemical bond.

[0013] (Conductive particles) As the conductive particles, known particles that have been conventionally used in conductive adhesives, anisotropic conductive films, and anisotropic conductive adhesives can be used.

[0014] The core particles in the conductive particles may be inorganic or organic, without any particular limitations. Examples of inorganic core particles include metal particles such as gold, silver, copper, nickel, palladium, and solder, alloys, glass, ceramics, silica, metal or nonmetal oxides (including hydrates), metal silicates including aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides, and carbon. On the other hand, examples of organic core particles include thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylic esters, polyacrylonitrile, polyacetal, ionomers, and polyesters, alkyd resins, phenolic resins, urea resins, benzoguanamine resins, melamine resins, xylene resins, silicone resins, epoxy resins, and diallyl phthalate resins. These may be used alone or in combination of two or more. A composite material of an organic substance and an inorganic substance may also be used. Examples include styrene-silica composite resin, acrylic-silica composite resin, crosslinked alkoxysilyl polymer-acrylic resin, polyorganosiloxane-silica, etc. Among these, core particles made of resin or a composite material of organic and inorganic substances are preferred because they have a smaller specific gravity than core particles made of metal, are less likely to settle, have excellent dispersion stability, and are easy to maintain electrical connection due to the elasticity of the resin. The composite material of organic and inorganic substances may have a core-shell structure.

[0015] When an organic substance is used as the core particle, it is preferable that the core particle does not have a glass transition temperature or that the glass transition temperature is greater than 100° C., since the shape of the core particle is easily maintained in the anisotropic conductive connection step and in the step of forming a metal film. When the core particle has a glass transition temperature, the glass transition temperature is preferably 200° C. or less, since the conductive particles are easily softened in the anisotropic conductive connection and the contact area is increased, making it easier to obtain electrical continuity. From this viewpoint, when the core particle has a glass transition temperature, the glass transition temperature is more preferably greater than 100° C. and less than 180° C., and particularly preferably greater than 100° C. and less than 160° C.

[0016] When an organic material is used as the core particle, if the organic material is a highly crosslinked resin, the glass transition temperature is hardly observed even when the measurement is attempted up to 200°C by the method described in the following examples. In this specification, such particles are also referred to as particles having no glass transition point, and such core particles may be used in the present invention. Specific examples of the core particle material having no glass transition temperature can be obtained by copolymerizing the monomer constituting the organic material exemplified above with a crosslinkable monomer. Examples of crosslinkable monomers include tetramethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide di(meth)acrylate, tetraethylene oxide (meth)acrylate, 1,6-hexane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimeterolpropane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, tetramethylolmethane tri(meth)acrylate, Examples of such hard organic materials include polyfunctional (meth)acrylates such as tetramethylolmethane tetra(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol di(meth)acrylate, glycerol tridi(meth)acrylate, etc., polyfunctional vinyl monomers such as divinylbenzene and divinyltoluene, silane-containing monomers such as vinyltrimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, etc., and monomers such as triallyl isocyanurate, diallyl phthalate, diallyl acrylamide, diallyl ether, etc. In particular, in the field of COG (Chip on Glass), core particles made of such hard organic materials are often used.

[0017] There is no particular limitation on the shape of the core particles. In general, the core particles are spherical. However, the core particles may be in a shape other than spherical, such as fibrous, hollow, plate-like or needle-like, and may have a large number of protrusions on the surface or may be amorphous. In the present invention, spherical core particles are preferred because they have excellent filling properties and are easy to coat with metal.

[0018] The particle size distribution of the powder consisting of core particles measured by the above-mentioned method has a certain range. In general, the range of the particle size distribution of a powder is represented by the coefficient of variation shown in the following formula (1). Coefficient of variation (%) = (standard deviation / average particle size) × 100 (1) A large coefficient of variation indicates a wide distribution, while a small coefficient of variation indicates a sharp particle size distribution. In the present invention, it is preferable to use core particles having a coefficient of variation of 30% or less, particularly 20% or less, and especially 10% or less. The reason for this is that when the conductive particles of the present invention are used as conductive particles in an anisotropic conductive film, there is an advantage that the contribution ratio effective for connection is high.

[0019] In addition, there are no particular limitations on other physical properties of the core particles. However, when the core particles are resin particles, the value of K defined by the following formula (2) is 100 N / mm 2 ~100000N / mm 2 and the recovery rate after 10% compressive deformation is preferably in the range of 1% to 100% at 20° C. By satisfying these physical property values, sufficient contact with the electrodes can be achieved without damaging the electrodes when they are pressure-bonded together. K value (N / mm 2 )=(3 / √2)×F×S -3 / 2 ×R -1 / 2 (2) (Here, F and S shown in formula (2) are the load value (N) and compression displacement (mm) at 10% compression deformation of the microsphere when measured using a microcompression tester MCTM-500 (manufactured by Shimadzu Corporation), and R is the radius of the microsphere (mm).)

[0020] The shape of the conductive particles is not particularly limited, although it depends on the shape of the core particles. For example, the conductive particles may be fibrous, hollow, plate-like, or needle-like, but spherical particles are preferred in terms of excellent packing properties and connectivity.

[0021] The conductive particles may have a smooth surface. The particles may have a plurality of protrusions protruding from their surfaces. If the protrusions are a continuum made of the same material as the metal coating, the electrical conductivity is further improved, which is preferable. More specifically, the metal coating has a flat portion and a plurality of protrusions protruding from the flat portion and forming a continuum from the flat portion, and the flat portion and the protrusions are preferably made of the same material. The term "continuum" means that the protrusions and flat portion of the metal coating are formed by a single process, and there is no part between the flat portion and the protrusions of the metal coating that impairs the sense of unity, such as a seam. However, with regard to the protrusions, the protrusions are made of a particle linkage formed by connecting a plurality of particles made of the material that constitutes the metal coating in a row, and it is acceptable for grain boundaries to be observed between the particles. Therefore, for example, when a core particle for forming a protrusion, such as a metal, a metal oxide, a non-metallic inorganic material such as graphite, or a conductive polymer is attached to the surface of a core particle, and the protrusion is formed from the core particle as a growth starting point, the flat portion and the protrusion are not formed in a single process, and therefore are not included in the continuum referred to in the present invention. However, it should be noted that a conductive particle having protrusions formed from such a core particle attached to a core particle and the core particle as a growth starting point is also within the scope of the present invention.

[0022] When the conductive particles have protrusions of the above-described configuration, the protrusions can break through the oxide film formed on the electrode surface when the electrodes are to be electrically connected, thereby reducing the connection resistance.

[0023] The height H of the protrusions is preferably 20 nm or more, particularly 50 nm or more, on average. The number of protrusions depends on the particle size of the conductive particles, but it is preferable that the number of protrusions is 1 to 20,000, particularly 5 to 5,000 per particle, from the viewpoint of further improving the conductivity of the conductive particles. The aspect ratio of the protrusions is preferably 0.5 or more, more preferably 1 or more. If the aspect ratio of the protrusions is large, it is advantageous because it can easily break through the above-mentioned oxide film. In addition, when an anisotropic conductive film is formed using conductive particles, it is considered that if the aspect ratio of the protrusions is large, the resin removal property is high, and therefore the conductivity is high. The aspect ratio is the ratio of the height H of the protrusions to the length D of the base of the protrusions, that is, a value defined as H / D.

[0024] The aspect ratio of the protrusions is as described above, and the length D of the base of the protrusions of the conductive particles is preferably 5 to 500 nm, particularly 10 to 400 nm, and the height H of the protrusions is preferably 5 to 500 nm, particularly 10 to 400 nm.

[0025] The metal coating in the conductive particles has electrical conductivity, and examples of the constituent metals include metals such as gold, platinum, silver, copper, iron, zinc, nickel, tin, lead, antimony, bismuth, cobalt, indium, titanium, antimony, bismuth, germanium, aluminum, chromium, palladium, tungsten, and molybdenum, as well as alloys thereof, and metal compounds such as ITO and solder. Among these, gold, silver, copper, nickel, palladium, and solder are preferred because of their low resistance, and nickel, palladium, gold, nickel alloys, palladium alloys, and gold alloys are particularly preferred because of their high binding with insulating particles. The metals in the conductive particles can be used alone or in combination of two or more. The nickel alloy also includes nickel-phosphorus, nickel-boron, and nickel-boron-phosphorus, and the palladium alloy also includes palladium-phosphorus and palladium-boron.

[0026] The metal coating may be a single layer structure or a laminated structure consisting of multiple layers. In the case of a laminated structure consisting of multiple layers, it is preferable from the viewpoint of reducing the connection resistance that the underlayer is made of nickel or a nickel alloy and the outermost layer is made of nickel, palladium, gold, a nickel alloy, a palladium alloy or a gold alloy, particularly when the metal coating is formed by electroless plating.

[0027] The thickness of the metal coating on the surface of the core particle is preferably 0.001 μm to 2 μm, and more preferably 0.005 to 1 μm.

[0028] Methods for forming a metal coating on the surface of core particles include dry methods using vapor deposition, sputtering, mechanochemical methods, hybridization methods, etc., and wet methods using electrolytic plating, electroless plating, etc. In addition, a metal coating may be formed on the surface of core particles by combining these methods, but conductive particles in which a metal coating is formed on the surface of core particles by electroless plating are preferred in that the particle surface can be uniformly and densely coated.

[0029] The average particle diameter of the conductive particles is preferably 0.1 μm or more and 50 μm or less, more preferably 1 μm or more and 30 μm or less. When the average particle diameter of the conductive particles is within the above range, the obtained coated particles do not cause a short circuit in a direction different from that between the opposing electrodes, and it is easy to ensure conduction between the opposing electrodes. In the present invention, the average particle diameter of the conductive particles is the average particle diameter measured using a scanning electron microscope (SEM). In addition, when the conductive particles are spherical in the scanning electron microscope image, the particle diameter measured using SEM is the diameter of a circular conductive particle image. When the insulating particles are not spherical, the particle diameter measured using SEM refers to the longest length (maximum length) of the line segments that cross the image of the conductive particles.

[0030] Specifically, the average particle size of the conductive particles is measured by the method described in the Examples.

[0031] Moreover, from the viewpoint of suppressing corrosion of electrodes and the like, it is preferable that the conductive particles contain few eluted impurity ions such as alkali metal ions, halogen ions, and organic acid ions.

[0032] (Insulating particles) The insulating particles used in the present invention are silica particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface thereof via a chemical bond.

[0033] Particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface of the silica particles via a chemical bond are preferably obtained by coating the silica particles with a silane coupling agent having a functional group that can be chemically converted into a sulfonic acid group (hereinafter, sometimes referred to as a "silane coupling agent having a functional group") and then converting the functional group into a sulfonic acid group, from the viewpoint that the sulfonic acid group that is firmly fixed and present on the surface of the silica particles will result in excellent adhesion to the conductive particles.

[0034] As the silica particles to be coated with a silane coupling agent having a sulfonic acid group (hereinafter, sometimes referred to as "silica particles (a)"), for example, those produced by growing particles from sodium silicate or an active silicic acid solution, those produced using an organic silicon compound as a raw material, vapor-phase silica, precipitated silica, etc. can be used.

[0035] The preferred physical property of the silica particles (a) is that the average particle size determined by a dynamic light scattering method is 5 to 500 nm, preferably 10 to 300 nm. When the average particle size of the silica particles (a) is within the above range, the insulating particles are easily adsorbed to the particle surfaces of the conductive particles in a uniformly dispersed state.

[0036] Examples of silane coupling agents having a functional group include silane coupling agents having a mercapto group or a sulfide group that can be converted to a sulfonic acid group by oxidation. The silane coupling agent having a mercapto group is a silica compound having a mercapto group and a hydrolyzable group, and is preferably represented by the following general formula (1). R 1 Si(OR 2 )3(1) (In the formula, R 1 R represents a hydrocarbon group having 1 to 8 carbon atoms and 1 to 3 mercapto groups, an alicyclic hydrocarbon group having 1 to 3 mercapto groups, or an aromatic hydrocarbon group having 6 to 8 carbon atoms and 1 to 3 mercapto groups. 2 represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 8 carbon atoms, an alicyclic hydrocarbon group having 3 to 8 carbon atoms, or an aromatic hydrocarbon group having 6 to 8 carbon atoms. 2 may be the same group or different groups.) Specific examples of the compound include 3-mercaptopropyltrimethoxysilane, 2-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, and 2-mercaptoethyltriethoxysilane.

[0037] The silane coupling agent having a sulfide group is a silica compound having a sulfide group and a hydrolyzable group, and an example thereof is bis(3-triethoxysilylpropyl) disulfide.

[0038] Particles in which a condensate of a silane coupling agent having a sulfonic acid group is fixed to the surface of silica particles (a) via a chemical bond can be obtained by a known method, for example, the method described in JP-A-2010-269985, JP-A-2013-41992, or J. Ind. Eng. Chem. Vol. 12, No. 6 (2006) pp. 911-917, etc. That is, by having a first step of contacting silica particles (a) with a silane coupling agent having a functional group to coat the surfaces of the silica particles (a) with the silane coupling agent having a functional group to obtain silica particles (a') coated with the silane coupling agent having a functional group, and then a second step of oxidizing the silica particles (a') coated with the silane coupling agent having a functional group with an oxidizing agent, it is possible to easily obtain particles in which a condensate of a silane coupling agent having a sulfonic acid group is fixed to the surface of the silica particles (a) via a chemical bond.

[0039] The coating amount of the silane coupling agent having a functional group is preferably 0.1 to 10 mass %, and more preferably 1 to 5 mass %, from the viewpoint of enabling the surface of the silica particles (a) to be uniformly coated.

[0040] In addition, the coating of silica particles (a) with a silane coupling agent having a functional group reduces the specific surface area of ​​the silica particles (a) by 1 nm 2 0.8 x 10 -24 ~6.6×10 -24 Molar, preferably 3.3 x 10 -24 x6.6x10 -24 It is preferably molar.

[0041] The first step is a step of coating silica particles (a) with a silane coupling agent having a functional group to obtain silica particles (a') coated with the silane coupling agent having a functional group.

[0042] The method for coating the silica particles (a) with a silane coupling agent having a functional group can be carried out by a wet method or a dry method.

[0043] When the coating treatment of the silica particles (a) with a silane coupling agent having a functional group is carried out by a wet method, the coating treatment method is as follows: 1) A method in which silica particles (a) are immersed in a solvent containing a silane coupling agent having a functional group at a desired concentration, and if necessary heated to promote the reaction between the silica particles (a) and the silane coupling agent having a functional group, to obtain a reaction liquid (A) containing silica particles (a') coated with a silane coupling agent having a functional group, and then, if necessary, spray-dried together with the solvent, or dried after solid-liquid separation, to obtain silica particles (a') coated with the silane coupling agent having a functional group. 2) A method in which a silane coupling agent having a functional group is added to a dispersion liquid containing silica particles (a) and a solvent, and the mixture is heated to 50 to 100°C to carry out a reaction, thereby obtaining a reaction liquid (B) containing silica particles (a') coated with a silane coupling agent having a functional group, and then, if necessary, spray drying the reaction liquid together with the solvent, or performing solid-liquid separation and drying to obtain silica particles (a') coated with a silane coupling agent having a functional group. The reaction liquid (A) and the reaction liquid (B) can be used as they are as the "dispersion containing silica particles (a') coated with a silane coupling agent having a functional group" described later.

[0044] Solvents that can be used in the wet method include alcohols such as methanol, ethanol, and propanol, or mixed solvents of these alcohols and water. In addition, commercially available silica sol can be used as the silica particles (a), and in the case of aqueous silica sol, alcohol can be added to make a mixed solution of alcohol and water, and for example, a silane coupling agent having a functional group can be added to this to carry out the above-mentioned operation 2).

[0045] When the coating treatment of the silica particles (a) with a silane coupling agent having a functional group is carried out by a dry method, examples of the coating treatment method include a method in which the silane coupling agent having a functional group and the silica particles (a) are mixed in a dry manner using a mechanical means such as a Henschel mixer or an air flow grinder, or a method in which the silane coupling agent having a functional group is diluted with a solvent, the diluted solution is mixed with the silica particles (a), and the resulting mixture is dried by heating.

[0046] In the present invention, in the first step, it is preferable to use silica particles (a') coated with a silane coupling agent having a functional group obtained by the wet method 2) because it is easy to obtain silica particles (a') coated with a silane coupling agent having a monodispersed functional group and it is easy to obtain coated particles with a high coverage rate.

[0047] The second step is a step of preparing a dispersion containing silica particles (a') coated with a silane coupling agent having a functional group obtained in the first step, and adding an oxidizing agent thereto for oxidation treatment to obtain particles in which a condensate of the silane coupling agent having a sulfonic acid group is fixed to the surface of the silica particles (a) via a chemical bond.

[0048] The dispersion liquid containing the silica particles (a') coated with the silane coupling agent having a functional group obtained in the first step and used in the second step can be prepared by using the reaction liquid (A) or reaction liquid (B) as it is for the one prepared by the wet method in the first step. On the other hand, the one prepared by the dry method in the first step can be prepared by dispersing the silica particles (a') coated with the silane coupling agent having a functional group obtained in the first step in a solvent again.

[0049] Examples of the solvent that can be used include alcohols such as methanol, ethanol, and propanol, and mixed solvents of these alcohols with water.

[0050] Usable oxidizing agents include hydrogen peroxide, peracetic acid, and perbenzoic acid, and it is particularly preferable to use hydrogen peroxide from the viewpoint of obtaining a product of high purity.

[0051] The amount of the oxidizing agent added is preferably 2 to 6 times by mole the amount of the silane coupling agent having a functional group, from the viewpoint of minimizing the amount of residual oxidizing agent.

[0052] The temperature of the oxidation reaction in the second step is not particularly limited, but is 5 to 100° C., preferably 20 to 100° C., and the reaction time, although depending on the reaction temperature, is usually 1 hour or more, preferably 2 to 40 hours.

[0053] After the reaction is completed, the mixture is spray-dried together with the solvent if necessary, or is separated into solid and liquid and then dried to obtain particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface of the silica particles (a) via a chemical bond.

[0054] (Coated particles) The coated particles of the present invention use, as insulating particles, silica particles (a) having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface thereof via a chemical bond. The surface of the conductive particles may be coated with the insulating particles by a wet method or a dry method.

[0055] In the dry method, the mixture is prepared by a mechanical means that exerts a strong shearing force. Apparatuses that can be used in the dry method include a high-speed mixer, a super mixer, a turbosphere mixer, an Eirich mixer, a Henschel mixer, a hybridization system, a Nauta mixer, a ribbon blender, a jet mill, and a cosmoizer.

[0056] The wet method is a method in which insulating particles and conductive particles are brought into contact with each other through a solvent under stirring, and the insulating particles are attached to the surfaces of the conductive particles. Examples of solvents that can be used include water, acetone, methanol, ethanol, and mixtures thereof. The temperature at which the insulating particles and conductive particles are brought into contact is not particularly limited, but is 5 to 100°C, preferably 10 to 50°C, and is sufficient even at around room temperature (25°C). The coated particles of the present invention can be obtained by recovering solids from the solvent by a conventional method, and washing and drying are performed as necessary.

[0057] Alternatively, the coated particles of the present invention may be obtained by a method comprising a first step of reacting a compound having, within the same molecule, a functional group (A) reactive with the metal coating in the conductive particle and a functional group (B) reactive with the sulfonic acid group in the insulating particle (hereinafter sometimes referred to as a "reactive compound") with the metal coating of the conductive particle, and then a second step of reacting the compound with the insulating particle.

[0058] Examples of the functional group (A) include a silane group, a silanol group, a carboxyl group, an amino group, an ammonium group, a nitro group, a hydroxyl group, a carbonyl group, a thiol group, a sulfonic acid group, a sulfonium group, a boric acid group, an oxazoline group, a pyrrolidone group, a phosphate group, and a nitrile group. Examples of the functional group (B) include an epoxy group, an amino group, a hydroxyl group, an isocyanate group, an oxazoline group, a carbodiimide group, and a halogen group.

[0059] The first step can be carried out by a known method, for example, the methods described in WO2003 / 025955 pamphlet, JP-A 2001-342377, JP-A 2003-26813, and the like.

[0060] The second step can be carried out in a wet or dry manner.

[0061] In the dry method, the mixture is prepared by a mechanical means that exerts a strong shearing force. Apparatuses that can be used in the dry method include a high-speed mixer, a super mixer, a turbosphere mixer, an Eirich mixer, a Henschel mixer, a hybridization system, a Nauta mixer, a ribbon blender, a jet mill, and a cosmoizer.

[0062] The wet method is a method in which insulating particles and conductive particles coated with a reactive compound are brought into contact with each other through a solvent under stirring, and the insulating particles are attached to the surfaces of the conductive particles coated with the reactive compound. Examples of solvents that can be used include water, acetone, methanol, ethanol, and mixed solvents thereof. The temperature at which the insulating particles and the conductive particles coated with a reactive compound are brought into contact is not particularly limited, but is 5 to 100°C, preferably 10 to 50°C, and is also sufficient even at around room temperature (25°C). The solid content is recovered from the solvent by a conventional method, and washed and dried as necessary to obtain the coated particles of the present invention. can be obtained.

[0063] The coated particles according to the present invention preferably have a coverage rate of insulating particles of 30% or more, preferably 30 to 100%, and particularly preferably 30 to 80%, from the viewpoint of achieving excellent electrical reliability when the coated particles are used to electrically connect upper and lower electrodes.

[0064] The coverage rate was calculated by counting the number n of insulating particles attached to the conductive particles using an SEM and using the following formula: The coverage rate used for evaluation is the average value of 20 coated particles. Coverage rate (%) = (n / N) x 100 N: The number of insulating particles when the insulating particles are arranged in close packing on the surface of a conductive particle N=4π(R+r) 2 / 2√3r 2 (R: radius of conductive particle (nm), r: radius of insulating particle (nm))

[0065] The coated particles according to the present invention use, as insulating particles, particles in which a condensate of a silane coupling agent having a sulfonic acid group is fixed to the particle surface of silica particles (a) via a chemical bond. In the particles in which a condensate of a silane coupling agent having a sulfonic acid group is fixed to the particle surface of the silica particles (a) via a chemical bond, the condensate of the silane coupling agent having a sulfonic acid group and the silica particles (a) are firmly fixed by chemical bonds due to a dehydration condensation reaction between a silanol group generated by hydrolysis of the silane coupling agent and a hydroxyl group on the surface of the silica particles (a). Meanwhile, the sulfonic acid group is firmly bonded to the metal film of the conductive particle or the functional group (B) of the reactive compound. Therefore, the coated particles of the present invention have excellent adhesion between the insulating particles and the conductive particles.

[0066] In addition, the coated particles according to the present invention may be conductive particles that have been surface-treated with a hydrophobizing agent. The presence of a hydrophobizing agent on the surface of the conductive particles provides excellent affinity with the insulating particles, and the coverage of the insulating particles can be further increased. Examples of the hydrophobizing agent include benzotriazole compounds, titanate coupling agents, higher fatty acids or derivatives thereof, phosphates and phosphites, etc. These may be used alone or in combination of two or more kinds, if necessary.

[0067] In this case, the insulating particles may be bonded to the conductive particles 1) via a hydrophobizing agent present on the particle surface of the conductive particles, or 2) directly to the particle surface of the conductive particles without the hydrophobizing agent, or may be bonded in a mixture of 1) and 2).

[0068] The benzotriazole compound is preferably one represented by the following general formula (2). [ka] (In the formula, A1 and A2 are the same or different and represent an alkyl group, an aryl group, a halogen atom, a hydroxyl group, an amino group, or a carboxyl group, and p1 and q1 are the same or different and represent an integer of 0 to 2.) A1 and A2 in the general formula (2) are an alkyl group, an aryl group, a halogen atom, a hydroxyl group, an amino group, or a carboxyl group. The alkyl group is preferably an alkyl group having 1 to 5 carbon atoms, such as a methyl group, an ethyl group, a propyl group, or a butyl group. The aryl group is preferably a phenyl group, a tolyl group, a xylyl group, or a naphthyl group. The halogen atom includes chlorine, bromine, and iodine. p1 and q1 in the general formula (2) are the same or different and are integers of 0 to 2. A1 and A2 may be the same or different groups.

[0069] Specific preferred examples of the benzotriazole-based compound represented by the general formula (2) include benzotriazole, 4-methylbenzotriazole, 5-methylbenzotriazole, 4-ethylbenzotriazole, 5-ethylbenzotriazole, 4,5-dimethylbenzotriazole, 4,6-dimethylbenzotriazole, 5,6-dimethylbenzotriazole, 4,5-diethylbenzotriazole, 4,6-diethylbenzotriazole, 5,6-diethylbenzotriazole, 4-phenylbenzotriazole, 5-phenylbenzotriazole, 4-chlorobenzotriazole, 5-chlorobenzotriazole, 4-carboxybenzotriazole, 5-carboxybenzotriazole, 4,5-dicarboxybenzotriazole, and 4,6-dicarboxybenzotriazole.

[0070] Examples of titanate-based coupling agents include those represented by the following formula (i) or formula (ii). (B 1 O)Ti(OB 2 )(OB 3 )(OB 4 ) (i) (In the formula, B 1 is an alkyl group, B 2 ~B 4are each a group selected from an alkyl group, an alkyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkenyl group, an alkenyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkanoyl group, a dialkylpyrophosphate group, and an alkylbenzenesulfonyl group, provided that B 2 ~B 4 At least one of the above is an alkanoyl group, a dialkylpyrophosphate group, or an alkylbenzenesulfonyl group. 1 and B 2 may join together to form a ring.)

[0071] (B 5 O)Ti(OB 6 )(OB 7 )(OB 8 )·[P(OB 9 )2OH]2(ii) (In the formula, B 5 ~B 8 are respectively an alkyl group, an alkyl group in which a methylene group other than the terminal group is substituted with an oxygen atom, an alkenyl group, or an alkenyl group in which a methylene group other than the terminal group is substituted with an oxygen atom. 9 is an alkyl group. In the above formula (i), B 1 ~B 4 Two or three of the groups may be the same; B 1 ~B 4 In the compound represented by formula (ii), B 5 ~B 8 Two or three of the groups may be the same; B 5 ~B 8 may all be different. 9 In the compound represented by formula (i), the number of alkanoyl groups, dialkylpyrophosphate groups or alkylbenzenesulfonyl groups is preferably 1 to 3, more preferably 2 to 3, and particularly preferably 3.

[0072] Examples of the alkyl group mentioned above include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, isopentyl group, 2-methylbutyl group, 1-methylbutyl group, n-hexyl group, isohexyl group, 3-methylpentyl group, 2-methylpentyl group, 1-methylpentyl group, heptyl group, octyl group, isooctyl group, 2-ethylhexyl group, 3,7-dimethyloctyl group, nonyl group, decyl group, undecyl group, dodecyl group, lauryl group, tetradecyl group, hexadecyl group, octadecyl group (including stearyl group), nonadecyl group, eicosyl group, triacontyl group, and tetracontyl group. Examples of the alkenyl group include groups in which one or more carbon-carbon single bonds of the above alkyl groups are changed to carbon-carbon double bonds.

[0073] The group in which a methylene group other than the terminal in an alkyl group is replaced with an oxygen atom is not an alkoxy group, but includes a group in which methylene groups in an alkyl group are interrupted by an oxygen atom. The same groups can be mentioned for a group in which a methylene group other than the terminal in an alkenyl group is replaced with an oxygen atom.

[0074] B 1 ~B 4 , B 5 ~B 8 The number of carbon atoms in the alkyl group represented by the formula (I), the group in which a methylene group other than the terminal in the alkyl group is substituted with an oxygen atom, the alkenyl group, and the group in which a methylene group other than the terminal in the alkenyl group is substituted with an oxygen atom is preferably 3 to 40, and more preferably 3 to 32. 2 ~B 4 The alkanoyl group represented by the formula (I) is preferably one having 2 to 40 carbon atoms. 2 ~B 4 The alkyl group of the dialkylpyrophosphate group represented by the formula (I) preferably has 3 to 40 carbon atoms. 2 ~B 4 The alkyl group of the alkylbenzenesulfonyl group represented by the formula (I) is preferably one having 3 to 40 carbon atoms. 9The alkyl group represented by the following formula (I) is preferably one having 3 to 40 carbon atoms.

[0075] B 1 and B 2 Examples of the ring formed by combining with the oxygen atom and titanium atom in formula (i) include -CH2-CH2- or -CH2-COO-.

[0076] Each group represented by the above formula (i) or (ii) may be substituted with a substituent, such as a halogen atom, an epoxy group, an amino group, a vinyl group, an acryl group, an isocyanate group, or a mercapto group.

[0077] Specific examples of titanate-based coupling agents used in the present invention include isopropyl triisostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraisopropyl(dioctyl phosphite) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, and the like. These may be used alone or in combination of two or more. These titanate coupling agents are commercially available, for example, from Ajinomoto Fine-Techno Co., Ltd.

[0078] The higher fatty acid is preferably a saturated or unsaturated linear or branched mono- or polycarboxylic acid, more preferably a saturated or unsaturated linear or branched monocarboxylic acid, and even more preferably a saturated or unsaturated linear monocarboxylic acid. The fatty acid preferably has 7 or more carbon atoms. The derivative refers to a salt or amide of the fatty acid.

[0079] The fatty acid or its derivative used in the present invention has a carbon number of the fatty acid of preferably 7 to 23, more preferably 10 to 20. Examples of such fatty acids or their derivatives include saturated fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, and stearic acid, unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, and arachidonic acid, and metal salts or amides thereof. Examples of metal salts of fatty acids include salts of alkali metals, alkaline earth metals, transition metals such as Zr, Cr, Mn, Fe, Co, Ni, Cu, and Ag, and metals other than transition metals such as Al and Zn, and are preferably polyvalent metal salts such as Al, Zn, W, and V. The fatty acid metal salt may be mono-, di-, tri-, or tetra-form depending on the valence of the metal. The fatty acid metal salt may be any combination of these.

[0080] As the phosphate ester and the phosphite ester, those having an alkyl group having 6 to 22 carbon atoms are preferably used. Examples of phosphate esters include hexyl phosphate, heptyl phosphate, monooctyl phosphate, monononyl phosphate, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl phosphate, monotetradecyl phosphate, and monopentadecyl phosphate. Examples of phosphite esters include hexyl phosphite, heptyl phosphite, monooctyl phosphite, monononyl phosphite, monodecyl phosphite, monoundecyl phosphite, monododecyl phosphite, monotridecyl phosphite, monotetradecyl phosphite, and monopentadecyl phosphite.

[0081] In the present invention, the hydrophobizing agent is preferably a triazole-based compound or a titanate-based coupling agent, in that it has excellent affinity with the insulating particles and is highly effective in increasing the coverage of the insulating particles, and in particular, benzotriazole, 4-carboxybenzotriazole, isopropyl triisostearoyl titanate, and tetraisopropyl (dioctyl phosphite) titanate are particularly preferred.

[0082] In the present invention, the hydrophobizing agent may be present on the surface of the conductive particle, and in that case, the hydrophobizing agent may be present on the entire surface of the conductive particle or only on a part of the surface. The hydrophobizing agent may also form a layer that covers a part or the entire surface of the conductive particle. The hydrophobizing agent may be present on the surface of the conductive particles as a condensation product thereof.

[0083] The method for surface-treating the conductive particles with a hydrophobizing agent is not particularly limited, and any known method can be used, such as a method in which the conductive particles and the hydrophobizing agent are mixed in a solvent. The solvent may be water or an organic solvent, or may be a mixed solvent of water and an organic solvent. Examples of the organic solvent include toluene, methanol, ethanol, propanol, butanol, isobutyl alcohol, acetone, methyl ethyl ketone, tetrahydrofuran, acetonitrile, N-methylpyrrolidone, and dimethylformamide. In a dispersion liquid in which conductive particles and a hydrophobizing agent are added to a solvent, the concentration of the hydrophobizing agent is 0.01 to 20% by mass. The concentration of the conductive particles in this dispersion liquid is 1 to 50% by mass. The dispersion liquid after the treatment is filtered and, if necessary, dried to obtain conductive particles having a hydrophobizing agent on the surface thereof.

[0084] In addition, as a method for coating the insulating particles on the particle surfaces of the conductive particles that have been surface-treated with a hydrophobizing agent, a method similar to the method for coating the insulating particles on the particle surfaces of the conductive particles described above can be used.

[0085] Taking advantage of the insulating properties between coated particles and the connectivity between opposing electrodes, the coated particles of the present invention are suitably used, for example, as an anisotropic conductive film (ACF), a heat seal connector (HSC), a conductive material for connecting electrodes of a liquid crystal display panel to a circuit board of a driving LSI chip, etc. In particular, they are suitably used as a conductive filler for conductive adhesives.

[0086] The conductive adhesive is preferably used as an anisotropic conductive adhesive that is disposed between two substrates on which a conductive base material is formed, and that adheres the conductive base material to conduct electricity by heating and pressurization. This anisotropic conductive adhesive contains the conductive particles of the present invention and an adhesive resin. The adhesive resin can be used without any particular limitation as long as it is insulating and is used as an adhesive resin. It may be either a thermoplastic resin or a thermosetting resin, and it is preferable that the adhesive performance is expressed by heating. Such adhesive resins include, for example, a thermoplastic type, a thermosetting type, an ultraviolet curing type, and the like. In addition, there are so-called semi-thermosetting types that show intermediate properties between the thermoplastic type and the thermosetting type, and composite types of a thermosetting type and an ultraviolet curing type. These adhesive resins can be appropriately selected according to the surface characteristics of the circuit board or the like to be adhered and the form of use. In particular, an adhesive resin that includes a thermosetting resin is preferable because it has excellent material strength after adhesion.

[0087] Specific examples of adhesive resins include those prepared using as the main component one or a combination of two or more selected from ethylene-vinyl acetate copolymer, carboxyl-modified ethylene-vinyl acetate copolymer, ethylene-isobutyl acrylate copolymer, polyamide, polyimide, polyester, polyvinyl ether, polyvinyl butyral, polyurethane, SBS block copolymer, carboxyl-modified SBS copolymer, SIS copolymer, SEBS copolymer, maleic acid-modified SEBS copolymer, polybutadiene rubber, chloroprene rubber, carboxyl-modified chloroprene rubber, styrene-butadiene rubber, isobutylene-isoprene copolymer, acrylonitrile-butadiene rubber (hereinafter referred to as NBR), carboxyl-modified NBR, amine-modified NBR, epoxy resin, epoxy ester resin, acrylic resin, phenol resin, silicone resin, etc. Among these, styrene-butadiene rubber and SEBS are preferable as thermoplastic resins because they have excellent reworkability. As thermosetting resins, epoxy resins are preferable. Of these, epoxy resins are most preferred because of their advantages of high adhesive strength, excellent heat resistance and electrical insulation, low melt viscosity, and ability to connect at low pressure.

[0088] As the epoxy resin, any commonly used epoxy resin can be used as long as it is a polyhydric epoxy resin having two or more epoxy groups in one molecule. Specific examples include novolac resins such as phenol novolac and cresol novolac, polyhydric phenols such as bisphenol A, bisphenol F, bisphenol AD, resorcin, and bishydroxydiphenyl ether, polyhydric alcohols such as ethylene glycol, neopentyl glycol, glycerin, trimethylolpropane, and polypropylene glycol, polyamino compounds such as ethylenediamine, triethylenetetramine, and aniline, and polyvalent carboxy compounds such as adipic acid, phthalic acid, and isophthalic acid, and glycidyl-type epoxy resins obtained by reacting epichlorohydrin or 2-methylepichlorohydrin. In addition, aliphatic and alicyclic epoxy resins such as dicyclopentadiene epoxide and butadiene dimer diepoxide can be mentioned. These can be used alone or in combination of two or more.

[0089] From the viewpoint of preventing ion migration, it is preferable to use high-purity adhesive resins in which impurity ions (Na, Cl, etc.) and hydrolyzable chlorine are reduced as the various adhesive resins mentioned above.

[0090] The amount of conductive particles used in the anisotropic conductive adhesive is usually 0.1 to 30 parts by mass, preferably 0.5 to 25 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the adhesive resin component. By keeping the amount of conductive particles within this range, increases in connection resistance and melt viscosity are suppressed, connection reliability is improved, and connection anisotropy can be sufficiently ensured.

[0091] In addition to the conductive particles and adhesive resin described above, the anisotropic conductive adhesive may contain additives known in the art. The amount of the additives may be within a range known in the art. Examples of other additives include tackifiers, reactive assistants, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizing agents, anti-degradation agents, heat resistance additives, thermal conductivity improvers, softeners, colorants, various coupling agents, or metal deactivators.

[0092] Examples of tackifiers include rosin, rosin derivatives, terpene resins, terpene phenol resins, petroleum resins, coumarone-indene resins, styrene resins, isoprene resins, alkylphenol resins, and xylene resins. Examples of reactive auxiliaries, i.e., crosslinking agents, include polyols, isocyanates, melamine resins, urea resins, utropines, amines, acid anhydrides, and peroxides. As epoxy resin curing agents, any agent having two or more active hydrogens per minute can be used without any particular limitations. Specific examples include polyamino compounds such as diethylenetriamine, triethylenetetramine, metaphenylenediamine, dicyandiamide, and polyamidoamine; organic acid anhydrides such as phthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride; and novolac resins such as phenol novolac and cresol novolac. These can be used alone or in combination of two or more. If necessary, a latent curing agent may be used. Examples of usable latent curing agents include imidazoles, hydrazides, boron trifluoride-amine complexes, sulfonium salts, aminimides, polyamine salts, dicyandiamide, and modified products thereof. These can be used alone or in combination of two or more.

[0093] The anisotropic conductive adhesive is manufactured using a manufacturing device commonly used in the technical field. For example, the adhesive resin is mixed with conductive particles and a curing agent or various additives as necessary, and is manufactured by mixing in an organic solvent when the adhesive resin is a thermosetting resin, or by melt-kneading at a temperature above the softening point of the adhesive resin, preferably about 50 to 150°C, when the adhesive resin is a thermoplastic resin. The anisotropic conductive adhesive thus obtained may be applied as a coating or in the form of a film. EXAMPLES

[0094] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. <Preparation of insulating particle samples> (Insulating Particles 1) In a reaction vessel, 34.1 g of methanol was added to 44.1 g of aqueous silica sol (SiO2: 22.7% by mass, water: 77.3% by mass) to obtain a dispersion. Next, 0.15 g of 3-mercaptopropyltrimethoxysilane was added to the dispersion while stirring, and the mixture was stirred for 20 minutes. Next, the reaction vessel was heated to 60°C and stirred for 3 hours to complete the reaction. Next, the reaction solution was cooled to room temperature (25° C.), and then 0.25 g of 31% by weight hydrogen peroxide solution was added and the reaction was carried out for 5 hours while boiling. After the reaction was completed, the solids were recovered by filtration, washed with methanol, and dried at 120°C under vacuum for 12 hours to obtain silica particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the particle surface via a chemical bond, which was designated as insulating particle 1. The aqueous silica sol used was commercially available and had a particle size of 219 nm as determined by dynamic light scattering.

[0095] (Insulating particles 2) In a reaction vessel, 35.9 g of methanol was added to 55.9 g of aqueous silica sol (SiO2: 22.7 mass%, water: 77.3 mass%) to obtain a dispersion. Next, 0.39 g of 3-mercaptopropyltrimethoxysilane was added to the dispersion while stirring, and the mixture was stirred for 20 minutes. Next, the reaction vessel was heated to 60°C and stirred for 3 hours to complete the reaction. Next, the reaction solution was cooled to room temperature (25° C.), and then 0.65 g of 31% by weight hydrogen peroxide solution was added and the reaction was carried out for 5 hours while boiling. After the reaction was completed, the solids were recovered by filtration, washed with methanol, and dried at 120°C under vacuum for 12 hours to obtain silica particles having a condensate of a silane coupling agent having a sulfonic acid group fixed to the particle surface via a chemical bond, which were designated as insulating particles 2. The aqueous silica sol used was commercially available and had a particle size of 144 nm as determined by dynamic light scattering.

[0096] (Insulating particles 3) 100 ml of pure water was added to a 200 ml four-neck flask equipped with a stirring blade. Then, 30.00 mmol of styrene monomer, 0.03 mmol of 4-(vinylbenzyl)triethylammonium chloride, and 0.50 mmol of 2,2'-azobis(2-methylpropionamidine)dihydrochloride as a polymerization initiator were added. Nitrogen was aerated for 15 minutes to expel dissolved oxygen, and the temperature was raised to 60°C and maintained for 6 hours to allow the polymerization reaction to proceed. The dispersion of fine particles after polymerization was passed through a SUS sieve with a mesh size of 150 μm to remove aggregates. The dispersion from which the aggregates had been removed was centrifuged to settle the fine particles, and the supernatant was removed. The obtained solid was washed with pure water to obtain spherical fine particles of poly(styrene / 4-(vinylbenzyl)triethylammonium chloride). These were designated as insulating particles 3. The average particle size of the obtained microparticles was 272 nm.

[0097] <Preparation of conductive particle samples> The conductive particles used were the following commercially available conductive particles. The average particle diameter of the conductive particles was determined by randomly extracting 200 particles from a scanning electron microscope (SEM) photograph (magnification 100,000 times), measuring their particle diameters, and averaging the results.

[0098] (Conductive Particles 1) Ni-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle size of 3 μm, in which the surface of spherical resin particles has a nickel coating with a thickness of 0.125 μm, were prepared. The resin particles were made of a crosslinkable acrylic resin and had a glass transition temperature of 120° C. The average particle size was determined by randomly extracting particles from a scanning electron microscope (SEM) photograph (magnification, 100,000 times), measuring the particle sizes of the particles, and averaging the results.

[0099] (Conductive particles 2) Ni-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle diameter of 3 μm were prepared, which had 1,030 protrusions on the surface of spherical resin particles, with an average height of 0.1 μm, an average base length of 0.197 μm, and an aspect ratio of 0.5, and a nickel coating with a thickness of 0.125 μm. The resin particles were made of a crosslinked acrylic resin and had a glass transition temperature of 120° C. The average particle diameter was measured in the same manner as for the conductive particles 1.

[0100] (Conductive particles 3) Gold-plated particles (manufactured by Nippon Chemical Industry Co., Ltd.) with an average particle size of 4.6 μm, which have a gold-nickel conductive layer on the surface of spherical resin particles, were used. The resin particles were made of crosslinkable acrylic resin and had a glass transition temperature of 120° C. The average particle size was determined by randomly extracting particles from a scanning electron microscope (SEM) photograph (magnification, 100,000 times), measuring their particle sizes, and averaging the results.

[0101] {Examples 1 to 6} An insulating particle dispersion liquid was prepared by adding pure water to make the total volume 20 ml, so that the solid content concentration of the insulating particles obtained above was 10,000 ppm. 50 mg of each conductive particle sample was added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. Next, the solid content was separated from the stirred dispersion using a membrane filter with 10 μm openings, washed with water, and dried to obtain a coated particle sample.

[0102] {Comparative Example 1} The insulating particle dispersion liquid was prepared by adding pure water and NaCl to the insulating particle 3 obtained above so that the solid content concentration was 10,000 ppm, the NaCl concentration was 25 mmol, and the total volume was 20 ml. 50 mg of the conductive particle sample 1 was added to this dispersion liquid, and the mixture was stirred at room temperature (25° C.) for 15 hours. Next, the solid content was separated from the stirred dispersion using a membrane filter with 10 μm openings, washed with water, and dried to obtain a coated particle sample.

[0103] (Coverage evaluation) The difference in coverage when insulating particles are coated on conductive particles was evaluated from the coated particles obtained in the examples and comparative examples. The results are shown in Table 1. The coverage was determined by the following method. <Method of measuring coverage> The number N of insulating particles when the insulating particles are arranged in close packing on the surface of a conductive particle was calculated using the following formula. N=4π(R+r) 2 / 2√3r 2 (R: radius of conductive particle (nm), r: radius of insulating particle (nm)) The number n of insulating particles attached to the conductive particles was counted using an SEM, and the coverage rate was calculated using the following formula. The results are shown in Table 1. Coverage rate (%) = (n / N) x 100 The coverage used in the evaluation was the average value for 20 conductive particles.

[0104] (Evaluation of adhesion) 1 g of the coated particles obtained in the examples and comparative examples was added to 100 mL of pure water and subjected to ultrasonic treatment for 2 minutes using an ultrasonic device (VS-D100, manufactured by VELVO-CLEAR) at an oscillation frequency of 24 kHz. The coverage of the resulting coated particles was calculated in the same manner as in the evaluation of the coverage, and the adhesion was calculated using the following formula to evaluate the adhesion, and the results are shown in Table 1. The higher the adhesion value, the less the insulating particles fell off due to ultrasonic treatment, which means that the adhesion between the conductive particles and the insulating particles is high. Adhesion rate (%) = (coverage rate after ultrasonic treatment / coverage rate before ultrasonic treatment) x 100

[0105] [Table 1]

[0106] Example 7 100 ml of pure water was added to the conductive particles 2 (5 g) obtained above, and the mixture was stirred to obtain a dispersion of conductive particles 2. 10 ml of a 1 mass % aqueous solution of benzotriazole was added to this dispersion, and the mixture was stirred for 5 minutes to perform a surface treatment. Thereafter, the mixture was filtered through a membrane filter with an opening of 2.0 μm, and conductive particles 2 having a benzotriazole layer on the surface were collected. The collected conductive particles 2 were washed with pure water, and then 100 ml of pure water was added to obtain a dispersion of conductive particles 2 having a benzotriazole layer on the surface. The insulating particles 1 obtained above were added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. After the insulating particles 1 were added, the solid-liquid concentration of the insulating particles 1 in the dispersion liquid was 10,000 ppm by mass. After removing the supernatant, the particles were washed with pure water and then vacuum dried at 50°C to obtain a coated particle sample. The coverage and adhesion of the obtained coated particle sample were evaluated in the same manner as in Examples 1 to 6, and the results are shown in Table 2.

[0107] {Example 8} 25 ml of toluene was added to the conductive particles 2 (5 g) obtained above, and the mixture was stirred to obtain a dispersion of conductive particles 2. 0.1 g of isopropyl triisostearoyl titanate (Ajinomoto Fine-Techno, Plainact KR-TTS) was added to this dispersion, and the mixture was stirred at room temperature for 20 minutes to perform surface treatment. After that, the mixture was filtered through a membrane filter with an opening of 2.0 μm, and conductive particles 2 having a titanate-based coupling agent layer on the surface were collected. 100 ml of a mixture of ethanol:pure water = 75:25 by mass was added to the collected conductive particles 2 to obtain a dispersion of conductive particles 2 having a titanate-based coupling agent layer on the surface. The insulating particles 1 obtained above were added to this dispersion liquid, and the mixture was stirred at room temperature (25°C) for 15 hours. After the insulating particles 1 were added, the solid-liquid concentration of the insulating particles 1 in the dispersion liquid was 10,000 ppm by mass. After removing the supernatant, the particles were washed with pure water and then vacuum dried at 50°C to obtain a coated particle sample. The coverage and adhesion of the obtained coated particle sample were evaluated in the same manner as in Examples 1 to 6, and the results are shown in Table 2.

[0108] [Table 2]

[0109] <Evaluation of electrical conductivity> An insulating adhesive containing 100 parts by mass of epoxy resin, 150 parts by mass of hardener, and 70 parts by mass of toluene was mixed with 15 parts by mass of the coated particle sample obtained in the example to obtain an insulating paste. This paste was applied to a silicone-treated polyester film using a bar coater, and then the paste was dried to form a thin film on the film. The obtained thin film-forming film was placed between a glass substrate with aluminum deposited on the entire surface and a polyimide film substrate with a copper pattern formed at a pitch of 50 μm, and an electrical connection was made. The conductivity of the coated particles was evaluated at room temperature (25 ° C, 50% RH) by measuring the conduction resistance between the substrates. The lower the resistance value, the higher the conductivity of the coated particles can be evaluated. The conductivity evaluation of the coated particles was performed as follows: a resistance value of less than 2 Ω was evaluated as "very good" (indicated by "◯" in Table 3), a resistance value of 2 Ω or more but less than 5 Ω was evaluated as "good" (indicated by "△" in Table 3), and a resistance value of 5 Ω or more was evaluated as "poor" (indicated by "x" in Table 3). The results are shown in Table 3.

[0110] [Table 3]

Claims

1. A coated particle, in which the surface of a conductive particle having a metal coating formed on the surface of a core particle is coated with an insulating particle, the conductive particle being surface-treated with a hydrophobizing agent selected from a benzotriazole-based compound and a titanate-based coupling agent, and the insulating particle being a particle having a condensate of a silane coupling agent having a sulfonic acid group fixed to the surface of a silica particle via a chemical bond.

2. 2. The coated particle according to claim 1, wherein the core particle is made of a resin or a composite material of an organic substance and an inorganic substance.

3. 3. The coated particle according to claim 1, wherein the metal coating is at least one coating selected from the group consisting of nickel, palladium, gold, a nickel alloy, a palladium alloy, and a gold alloy.

4. 4. The coated particle according to claim 1, wherein the conductive particle has a plurality of protrusions on the metal coating.

5. The coated particles described in any one of claims 1 to 4, characterized in that the insulating particles are obtained by coating silica particles with a silane coupling agent having a functional group that can be chemically converted into a sulfonic acid group, and then converting the functional group into a sulfonic acid group.

6. 6. The coated particle according to claim 5, wherein the silane coupling agent having a functional group that can be chemically converted into a sulfonic acid group is a silane coupling agent having a mercapto group or a sulfide group.

7. A conductive material comprising the coated particles according to claim 1 and an insulating resin.

Citation Information

Patent Citations

  • Low-resistance inorganic powder

    JP1998007932A

  • Method for forming metal wiring and metal wiring board manufactured by the same

    JP2003298209A

  • Circuit connecting material, film-like-circuit connecting material using the same circuit connecting material, circuit-member connecting structure, and circuit-member connecting method

    JP2010277997A

  • Conductive coating composition

    JP2011228222A

  • Conductive particles with insulating particles, conductive material, and connection structure

    JP2014029857A